Die-hard plastic deformation behavior in an ultrahigh-strength Fe–Ni–Al–C alloy. (May 2015) - Furuta, T.; Kuramoto, S.; Ohsuna, T.; Oh-ishi, K.; Horibuchi, K.
Abstract : An important property of metallic materials is their ability to deform plastically. Ductility enables materials to be formed into various shapes and guarantees reliability under structural use. However, there is a trade-off relationship between ductility and strength. Here, we show a cold-worked Fe–24.6%Ni–5.8%Al–0.44%C alloy having yield strength of approximately 2 GPa, and a uniform elongation of over 20%. Activation of two or more deformation mechanisms is considered to be responsible for this "die-hard" plastic deformation with continuous, inhomogeneous strain hardening.